Is early exposure to pornography a risk factor for sexual compulsivity? Findings from an online survey among young Croatian adults - Štulhofer, Aleksandar (Array, 2008)
The aim of this retrospective study was to assess the relationship between early exposure to pornography and sexual compulsivity among Croatian young adults. Using online survey data on pornography use and sexual behavior among 1528 heterosexual women and men aged 18-25, we tested a hypothesis that pornography use at the age of 14 is a marker for sexual compulsivity in late adolescence and young adulthood. After satisfactory reliability of a 4-item subscale of the Sexual Compulsiveness Scale (Kalichman & Rompa, 1995) was confirmed in this sample, construct validity of this composite indicator focused on out of control sexual thoughts and behaviors was assessed. High sexual compulsivity was associated with sexual risk taking, though mainly among women, decreased levels of relationship intimacy and lesser sexual contentment. However, we found no significant association between early exposure to pornography and high sexual compulsivity either among men or women.